A method for measuring banana pseudo-stem phenotypic parameters based on handheld mobile LiDAR and IMU fusion - Yang, Zhou; Jiang, Qiming; Duan, Jieli; Jin, Mohui; Fu, Han; Xu, Xing (Frontiers in Plant Science, 2024)
Diameter and height are crucial morphological parameters of banana pseudo-stems, serving as indicators of the plant's growth status. Currently, in densely cultivated banana plantations, there is a lack of applicable research methods for the scalable measurement of phenotypic parameters such as diameter and height of banana pseudo-stems. This paper introduces a handheld mobile LiDAR and Inertial Measurement Unit (IMU) fused laser scanning system designed for measuring phenotypic parameters of banana pseudo-stems within banana orchards. To address the challenges posed by dense canopy cover in banana orchards, a distanceweighted feature extraction method is proposed. This method, coupled with Lidar-IMU integration, constructs a three-dimensional point cloud map of the banana plantation area. To overcome difficulties in segmenting individual banana plants in complex environments, a combined segmentation approach is proposed, involving Euclidean clustering, Kmeans clustering, and threshold segmentation. A sliding window recognition method is presented to determine the connection points between pseudo-stems and leaves, mitigating issues caused by crown closure and heavy leaf overlap. Experimental results in banana orchards demonstrate that, compared to manual measurements, the mean absolute errors and relative errors for banana pseudo-stem diameter and height are 0.2127cm(4.06%) and3.52cm(1.91%), respectively. These findings indicate that the proposed method is suitable for scalable measurements of banana pseudostem diameter and height in complex, obscured environments, providing a rapid and accurate inter-orchard measurement approach for banana plantation managers.